Enhanced cytotoxicity of imidacloprid by biotransformation in isolated hepatocytes and perfused rat liver - Bizerra, Paulo F.V. [UNESP]; Guimarães, Anilda R.J.S. [UNESP]; Miranda, Camila A. [UNESP]; Constantin, Rodrigo P.; Utsunomiya, Karina S.; Gilglioni, Eduardo H.; Constantin, Jorgete; Ishii-Iwamoto, Emy L.; Maioli, Marcos A. [UNESP]; Mingatto, Fábio E. [UNESP] (Elsevier, 2020)
Imidacloprid (IMD) is a neonicotinoid insecticide widely used in crops, pets, and on farm animals for pest control, which can cause hepatotoxicity in animals and humans. In a previous study using isolated rat liver mitochondria, we observed that IMD inhibited the activity of FoF1-ATP synthase. The aim of this study was to evaluate the effects of IMD on rat isolated hepatocytes and perfused rat liver, besides the influence of its biotransformation on the toxicological potential. For the latter goal, rats were pretreated with dexamethasone or phenobarbital, two classical cytochrome P-450 stimulators, before hepatocytes isolation or liver perfusion. IMD (150 and 200 μM) reduced state 3 mitochondrial respiration in digitonin-permeabilized cells that were energized with glutamate plus malate but did not dissipate the mitochondrial membrane potential. In intact (non-permeabilized) hepatocytes, the intracellular ATP concentration and cell viability were reduced when high IMD concentrations were used (1.5–3.0 mM), and only in cells isolated from dexamethasone-pretreated rats, revealing that IMD biotransformation increases its toxicity and that IMD itself affects isolated mitochondria or mitochondria in permeabilized hepatocytes in concentrations that do not affect mitochondrial function in intact hepatocytes. Coherently, in the prefused liver, IMD (150 and 250 μM) inhibited gluconeogenesis from alanine, but without affecting oxygen consumption and urea production, indicating that such effect was not of mitochondrial origin. The gluconeogenesis inhibition was incomplete and occurred only when the rats were pretreated with phenobarbital, signs that IMD biotransformation was involved in the observed effect. Our findings reveal that changes in hepatic energy metabolism may be acutely implicated in the hepatotoxicity of IMD only when animals and humans are exposed to high levels of this compound, and that IMD metabolites seem to be the main cause for its toxicity.
Keywords: Cellular structure; Energy metabolism; Gluconeogenesis; Insecticides; Liver; Toxicity